Effects of dynamic pedal motion and static disorder on thermal expansion within halogen-bonded co-crystals. (4th November 2019) - Juneja, Navkiran; Unruh, Daniel K.; Bosch, Eric; Groeneman, Ryan H.; Hutchins, Kristin M.
Abstract : Thermal expansion is investigated for halogen-bonded co-crystals containing molecules that exhibit dynamic motion, lack motion ability, or experience static disorder. Abstract : The contribution of molecular pedal motion, static disorder, or motion inability to the thermal expansion behavior of isostructural halogen-bonded co-crystals is reported.